Supporting Logistics Management to Anticipate Covid 19 Using the “Retail Direct Order” Concept - Purwadi, Purwadi; Y., Syahruddin; Ilmi, Zainal; Sampeliling, Alexander (Journal of Telecommunications and the Digital Economy, 2022)
The Covid-19 that has hit the world since the end of 2019 has had a considerable impact on the Indonesian economy, especially on business people. This paper considers how businesses in Indonesia could benefit from implementing a Retail Direct Order (RDO) process to respond to social changes, particularly restrictions on movement, brought about by the pandemic. The paper first reviews the literature on supply chain management and logistics and the effects on them due to greater digitization of businesses, operational automation and globalization. It then proposes how RDO can assist businesses in Indonesia – especially department stores, supermarkets, convenience stores, and non-store retailers – to adapt to the new business environment. One benefit of properly managed RDO is to reduce panic buying by supporting a more dependable supply of goods.